Pengembangan Panduan Digital Wisata Halal Berbahasa Arab Berbasis Budaya Indonesia: Menyelami Kebutuhan Wisatawan Muslim - Nuruddin, Nuruddin; Syarfuni, Syarfuni; Ilham, Andri; Abidin, Jenal; Arifin, Ahmad (Institut Agama Islam Negeri (IAIN) Metro, 2023)
This study aims to analyze the need for a digital guide to halal tourism in Arabic language based on Indonesian culture in Kabupaten Aceh Besar, Lombok Barat, and Gorontalo. The primary objectives are to provide practical and quick information about halal tourism, enhance domestic and international visits, and promote the unique cultural heritage of these three regions. The research adopts the Borg and Gall development model. The identification of the guide's needs utilizes data from documentation and questionnaires filled out by tourists, hotel managers, village administrators, tourism department officials, and travel companies. The study concludes that a digital Arabic-language halal tourism guide needs to be developed in terms of content (halal facilities, recreational activities, types of tourism), culture (information on local culture and permissible practices), and technology (application-based design for convenient access to tourism information).